Analisis Kinerja Ruas Jalan di Kecamatan Pelaihari Kabupaten Tanah Laut - Jihan Alya Nabillah; Hafsha Yanti Siregar (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Pelaihari District with the largest population in Tanah Laut Regency, as well as the road sections in Pelaihari District that are of concern are the main routes connecting several areas, namely Jalan A. Yani, Jalan Pancasila, Jalan KH. Mansyur. The roads above have an important role in supporting community mobility and economic activities in the region. The purpose of this study was to determine the performance of the road sections in Pelaihari District and to determine the worst Level of Service (LOS) value of the 3 roads reviewed. Analysis of road section performance using the 1997 Indonesian Road Capacity Manual method (MKJI 1997). The primary data needed are traffic volume data and road geometric data. Secondary data in the form of research location data and the population of Tanah Laut Regency. The results of data processing showed that the peak volume of vehicles that occurred on Jalan A. Yani, namely at 14.00-15.00 WITA was 1082.35 smp/hours, the peak volume of vehicles on Jalan Pancasila and Jalan KH. Mansyur obtained at 17:00-18:00 WITA respectively at 734.4 smp/hours and 598.2 smp/hours. Where the worst saturation degree value was obtained on Pancasila Street, which was 0.64 with Level of Service category C with stable flow information, with this value proving that the performance of the road section in Pelaihari District is still quite good.